Cardiac implantable electrical devices in women. Issue 2 (26th February 2018) - Elango, Kalaimani; Curtis, Anne B.
Abstract : Clinical trials have demonstrated the benefits of cardiac implantable electrical devices, which include pacemakers, implantable cardioverter‐defibrillators (ICDs), and cardiac resynchronization therapy (CRT), with respect to key clinical outcomes and survival. Women more often require permanent pacing for sick sinus syndrome, whereas atrioventricular block is more common in men. Women appear to have a higher incidence of complications with pacemaker implantation, as well as with ICD and CRT implantation. The indications for ICDs and CRT do not have any distinctions based on sex, and outcomes are comparable in men and women. In fact, women often seem to have better outcomes with CRT compared with men. Despite the demonstrated benefits of these devices, ICDs and CRT are underutilized in women. In this review, we explore sex differences in utilization, outcomes, and complications with pacemakers, ICDs, and CRT.